ORIENTAL: BUDAYA INDIS DALAM TETRALOGI PULAU BURU KARYA PRAMOEDYA ANANTA TOER (Oriental: Indis Culture in the Study of Buru Tetralogy by Pramoedya Ananta Toer) - Puji Retno Hardiningtyas (SAWERIGADING, 2014)
The Buru tetralogy consists of Bumi Manusia, Anak Semua Bangsa, Jejak Langkah, and Rumah Kaca. The fourth novel has coherence and similarity of themes, namely the domination of indigenous resistance Java feudalism (priyayi) and Dutch colonial, indigenous colonial antiracism culture and the birth of Indies culture (East and West). The objective of this research is to describe 1) the discourse of the blending of Eastern and Western cultures orientalism; 2) representation of Indigenous and Colonial as a consequence of the relationship between the colonized and the colonizers by using the post-colonial theory. The method of this research is the qualitative-interpretation-understanding (verstehen-hermeneutic-qualitative). The Cue of the power relations between East and West is characterized by the interaction of Western and Eastern cultures, known as the seven cultural universal. Meanwhile, repression between colonized and colonizer is revealed on exclusion and racial disparities felt by Natives in European society. Therefore, Orientalism as a reference to identify on the East, as the Indonesian identity has weaknesses, advantages, strangeness, and exotic causing the East is unmatched.